Microstructural developments of poly (p-phenylene terephthalamide) fibers during heat treatment process: a review - Dawelbeit Ahmed; Zhong Hongpeng; Kong Haijuan; Liu Jing; Ma Yu; Yu Muhuo (Materials Research, 2014)
Poly (p-phenylene terephthalamide) fibers prepared by wet or dry-jet wet spinning processes have a notable response to very brief heat treatment (seconds) under tension. The modulus of the as-spun fiber can be greatly affected by the heat treatment conditions (temperature, tension and duration). The crystallite orientation and the fiber modulus will increase by this short-term heating under tension. Poly (p-phenylene terephthalamide) fibers have a very high molecular orientation (orientation angle 12-20°). Kevlarï and Twaronï fibers are poly (p-phenylene terephthalamide) fibers. This review reports for PPTA fibers the heat treatment techniques, devices and its process conditions. It reports in details the structural relationships between the fiber properties which are influenced by the heat treatment process. In particular, focused deeply on the effect of the crystal structure and the morphology of the fibers on the mechanical properties of PPTA fibers.